2021
DOI: 10.25186/.v16i.1854
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cross laminated timber panels made of Pinus oocarpa and Coffea arabica waste

Abstract: The growth of the civil construction sector, made necessary to develop alternative products made of sustainable materials. Within this context came the cross laminated timber panels (CLT), which are formed by gluing veneer arranged at 90°, which provide high strength and great versatility, as constructive elements. This research aimed to evaluate the chemical properties of the particles of both materials and evaluate the performance of CLT panels made with Pinus oocarpa and waste wood from Coffea arabica. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
1
1
1
Order By: Relevance
“…wood are shown in Table 1. The average value obtained in this study for extractives was lower than that reported by Furtini et al (2021) who obtained an average of 7,38 % for ocote pine (Pinus oocarpa Schiede ex Schltdl.) wood.…”
Section: Physical and Chemical Characterization Of The Lignocellulosi...contrasting
confidence: 87%
“…wood are shown in Table 1. The average value obtained in this study for extractives was lower than that reported by Furtini et al (2021) who obtained an average of 7,38 % for ocote pine (Pinus oocarpa Schiede ex Schltdl.) wood.…”
Section: Physical and Chemical Characterization Of The Lignocellulosi...contrasting
confidence: 87%
“…They can also delay the adhesive evaporation rate, increasing the pressing time (IWAKIRI; TRIANOSKI, 2020). *averages followed by the same letter, in the column, do not differ from each other by the Scott-Knott test, at a significance level of 5%.For insoluble lignin, the values obtained in this study are in agreement with the literature Furtini et al (2021),. for example, obtained an average content of 29.20% for pine wood.…”
supporting
confidence: 90%
“…Nevertheless, they showed higher thermal resistance than CFPF and REPF samples due to their greater thickness. Although thermal resistance of cross-laminated timber made with coconut wood panels (CTCP) showed a low value (lower than 0.5 m 2 •K•W -1 , compared to BCFB), they had a higher RSI value than the maximum value of laminated timber made with Pinus Oocarpa Schiede ex Schlectendahl and Coffea Arabica L. waste (0.115 m 2 •K•W -1 at 30 mm thickness (Furtini et al 2021)). Therefore, the CTCP may be used as insulation materials for building applications.…”
Section: Results and Discussion Thermal Resistancementioning
confidence: 99%